Strategic Alliances in the Biotechnology Industry: A Systematic Literature Review of Drivers, Outcomes, and Future Research Directions - Cikal Rambasae N; Wiwik Ariska (School of Life Sciences and Technology, Institut Teknologi Bandung, 2026)
Strategic alliances play a pivotal role in the innovation-driven and uncertain landscape of the biotechnology industry. This study consolidates fragmented insights through a systematic literature review (SLR) of 161 peer-reviewed articles (1985–2025), following the PRISMA framework and combining bibliometric and thematic analyses. The review maps intellectual structures, thematic clusters, and geographical trends. Findings show that the field is anchored in innovation, biotechnology, and strategic planning, with strong contributions from the United States, while areas such as agricultural biotechnology, sustainability, and human capital remain underexplored. Thematic mapping indicates mature versus emerging themes, highlighting the rising importance of digitalization, inclusive innovation, and dynamic capabilities. Beyond mapping intellectual evolution, this review contributes theoretically by clarifying the role of alliances as vehicles for capability building, risk sharing, and knowledge flows. Methodologically, it demonstrates the value of integrating bibliometric and thematic approaches in systematic reviews. Practically, it offers guidance for managers and policymakers seeking collaborative solutions to address global health, environmental, and technological challenges.